Cardiac Toxicity From Adjuvant Targeting Treatment for Breast Cancer Post-Surgery - Fu, Zhenkun; Lin, Zhoujun; Yang, Mao; Li, Chenggang (Frontiers in Oncology, 2022)
Breast cancer is one of the most prevalent type of cancers worldwide, especially for females. Surgery is the preferred treatment for breast cancer, and various postoperative adjuvant therapies can be reasonably used according to different pathological characteristics, especially traditional radiotherapy, chemotherapy and endocrine therapy. In recent years, targeting agent therapy has also become one of the selective breast cancer treatment strategies, including anti-HER-2 drugs, CDK4/6 inhibitor, poly ADP-ribose polymerase inhibitor, PI3K/AKT/mTOR pathway inhibitor, ER targeting drugs and aromatase inhibitor. Because of the different pathologic mechanisms of these adjuvant therapies, each of the strategies may cause cardiotoxicity in clinic. The cardiac adverse events of traditional endocrine-therapy， radiotherapy and chemotherapy for breast cancer have been widely detected in clinic, however, the targeting therapy agents have been paid more attention with the extension of application. This review will summarize the cardiac toxicity of various adjuvant therapies for breast cancer, especially for targeting drug therapy.